Analisis Penataan Self-Portrait Berbasis Seni - Sarwo Nugroho; Ichsan Ichsan; Fa’iqah Salsabil Qadiriyyah (STEKOM PRESS, 2022)
The aim of this study is to describe the development of an innovative art-based analytical method in portrait methodology. This article exemplifies how forms of multimodal analysis can be integrated into portraiture frameworks and provides a fluid qualitative